В „утробата на кита”, или „тихият вик” на българските поети през 60-те и 70-те години на ХХ век - Кръстева, Гергина (Wydawnictwo Nauka i Innowacje, 2014)
This article entitled unassumingly aims at reminding – just in a cursory way, but with a substantial degree of certainty, too, in their literary and historical justification – of a specific list of names of Bulgarian poets, whose „discontent” and/or „disappointment” with the totalitarian regime in Bulgaria create the history of the dissent, which found its expression in the alternative lyrical thinking and writing in the period of socialist realism during the decades of the sixties and the seventies of the twentieth century.
In the „Whale’s Womb” or the „Silent Outcry” of the Bulgarian Poets of the 1960s and 1970s
Keywords: lyrics; ideological canon; alternative; dissent; socialist realism